Usefulness of peripapillary nerve fiber layer thickness assessed by optical coherence tomography as a biomarker for Alzheimer's disease. Issue 1 (December 2018) - Sánchez, Domingo; Castilla-Marti, Miguel; Rodríguez-Gómez, Octavio; Valero, Sergi; Piferrer, Albert; Martínez, Gabriel; Martínez, Joan; Serra, Judit; Moreno-Grau, Sonia; Hernández-Olasagarre, Begoña; Rojas, Itziar; Hernández, Isabel; et al.
Abstract The use of optical coherence tomography (OCT) has been suggested as a potential biomarker for Alzheimer's Disease based on previously reported thinning of the retinal nerve fiber layer (RNFL) in Alzheimer's disease's (AD) and Mild Cognitive Impairment (MCI). However, other studies have not shown such results. 930 individuals (414 cognitively healthy individuals, 192 probable amnestic MCI and 324 probable AD) attending a memory clinic were consecutively included and underwent spectral domain OCT (Maestro, Topcon) examinations to assess differences in peripapillary RNFL thickness, using a design of high ecological validity. Adjustment by age, education, sex and OCT image quality was performed. We found a non-significant decrease in mean RNFL thickness as follows: control group: 100, 20 ± 14, 60 µm, MCI group: 98, 54 ± 14, 43 µm and AD group: 96, 61 ± 15, 27 µm. The multivariate adjusted analysis revealed no significant differences in mean overall (p = 0.352), temporal (p = 0, 119), nasal (p = 0, 151), superior (p = 0, 435) or inferior (p = 0, 825) quadrants between AD, MCI and control groups. These results do not support the usefulness of peripapillary RNFL analysis as a marker of cognitive impairment or in discriminating between cognitive groups. The analysis of other OCT measurements in other retinal areas and layers as biomarkers for AD should be tested further.